1 |
n+1 |
1 |
n+2 |
1 |
2n |
∴f(n+1)=
1 |
n+2 |
1 |
n+3 |
1 |
2n |
1 |
2n+1 |
1 |
2n+2 |
∴f(n+1)-f(n)=(
1 |
n+2 |
1 |
n+3 |
1 |
2n |
1 |
2n+1 |
1 |
2n+2 |
1 |
n+1 |
1 |
n+2 |
1 |
2n |
=
1 |
2n+1 |
1 |
2n+2 |
1 |
n+1 |
=
1 |
2n+1 |
1 |
2n+2 |
故答案为:
1 |
2n+1 |
1 |
2n+2 |
1 |
n+1 |
1 |
n+2 |
1 |
2n |
1 |
n+1 |
1 |
n+2 |
1 |
2n |
1 |
n+2 |
1 |
n+3 |
1 |
2n |
1 |
2n+1 |
1 |
2n+2 |
1 |
n+2 |
1 |
n+3 |
1 |
2n |
1 |
2n+1 |
1 |
2n+2 |
1 |
n+1 |
1 |
n+2 |
1 |
2n |
1 |
2n+1 |
1 |
2n+2 |
1 |
n+1 |
1 |
2n+1 |
1 |
2n+2 |
1 |
2n+1 |
1 |
2n+2 |